2023
DOI: 10.1017/cts.2023.17
|View full text |Cite
|
Sign up to set email alerts
|

Competencies supporting high-performance translational teams: A review of the SciTS evidence base

Abstract: A translational team (TT) is a specific type of interdisciplinary team that seeks to improve human health. Because high-performing TTs are critical to accomplishing CTSA goals, a greater understanding of how to promote TT performance is needed. Previous work by a CTSA Workgroup formulated a taxonomy of 5 interrelated team-emergent competency “domains” for successful translation: 1). affect, 2). communication, 3). management, 4). collaborative problem-solving, and 5). leadership. These Knowledge Skills and Atti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
38
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 7 publications
(39 citation statements)
references
References 146 publications
1
38
0
Order By: Relevance
“…A recent scoping review of the SciTS evidence base identified 15 team-emergent competencies whose expert application leads to enhanced team performance (listed in Table 1) [14]. In this analysis, observable behaviors of the KSA were described along a continuum from "novice" to "expert."…”
Section: Origins and Development Of Team-emergent Ksas During Tt Matu...mentioning
confidence: 99%
See 1 more Smart Citation
“…A recent scoping review of the SciTS evidence base identified 15 team-emergent competencies whose expert application leads to enhanced team performance (listed in Table 1) [14]. In this analysis, observable behaviors of the KSA were described along a continuum from "novice" to "expert."…”
Section: Origins and Development Of Team-emergent Ksas During Tt Matu...mentioning
confidence: 99%
“…Shown are the TT competency domains[4]; specific competencies supporting each[14] are also listed, with a description of knowledge, skills, and attitudes.Journal of Clinical and Translational Science…”
mentioning
confidence: 99%
“…Affect is a state where TT members share concern, empathy, and regard [11,12], which in turn increases team members' commitment [13] and overall team performance [14]. Within this domain, we identified three foundational competencies necessary for Affect - (1).…”
Section: Leadership Behaviors and The Enhancement Of Teamemergent Com...mentioning
confidence: 99%
“…Idealized influence promotes Communication by empowering team members to establish communication lines with other team members and to seek out their expertise [33]. Additional behaviors include articulating a vision and conducting team building activities that foster communication and knowledge sharing [16,34]. A study of project management teams has shown that transformational leadership behaviors promote within-team knowledge sharing by establishing cooperative norms for how information is exchanged [35].…”
Section: Leadership Behaviors and The Enhancement Of Teamemergent Com...mentioning
confidence: 99%
See 1 more Smart Citation